PERSONAL FINANCIAL MANAGEMENT IN COLLEGE STUDENTS: THE IMPACT OF FINANCIAL KNOWLEDGE AND ATTITUDE ON SAVING BEHAVIOR - Fahri Haikal; Putri Sarah Olivia; Alamsyah Siregar; Suyanto Walidi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study is motivated by the low level of financial literacy among university students and the increasing complexity of personal financial management in the modern era. Financial knowledge and financial attitude are considered important factors influencing students’ saving behavior; however, empirical studies integrating these two variables are still limited, particularly in the Indonesian context.Methods: This research employs a quantitative approach using primary data collected through an online questionnaire distributed to 200 university students in the DKI Jakarta area. A purposive sampling technique was applied, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).Results: The findings reveal that financial knowledge has a positive and significant effect on both financial attitude and saving behavior. Financial attitude also has a positive and significant influence on saving behavior. Furthermore, financial attitude plays a stronger role in influencing saving behavior compared to the direct effect of financial knowledge.Conclusion and suggestions: The study concludes that students’ saving behavior is shaped by the interaction between cognitive factors (financial knowledge) and affective factors (financial attitude). Therefore, it is recommended that educational institutions and policymakers enhance financial literacy programs by not only improving knowledge but also fostering positive financial attitudes to promote better saving behavior among students. Keywords: Behavioral Finance; Financial Attitude; Financial Knowledge; Financial Literacy; Saving Behavior